Prevalence of severe depression in medical students of the University of Boyacá - Velasco Castro, Julio César; Ayala Lozano, Mario Nicolás; Ojeda Alba, Julieth Lorena; Fonseca García, Tania Liovef; Vargas Rodríguez, Ledmar Jovanny; García Agudelo, Lorena (Interdisciplinary Journal of Epidemiology and Public Health, 2023)
Introduction: Depression is characterized by the presence of manifestations that influence the person’s mood and can generate systemic involvement as the disease progresses. Objective: To identify the prevalence of depression in medical students at the University of Boyacá between March 26 and June 10, 2021. Material and methods: Observational, descriptive and retrospective study. We included 105 medical students who participated voluntarily by means of a survey with Google forms and the Zung scale. The prevalence of depression severity was identified, sociodemographic data were obtained and risk factor analysis was performed. Results: Of the 105 respondents, 75.2% were female and 24.8% were male. The age range was 16 to 39 years; the most representative age was 21 years. Nineteen percent had a family member with depression (2.9%), bipolar affective disorder (4.8%), among others. Mild depression was present in 24.7%, 46.6% moderate and 3.8% severe in the female sex, compared to men, 10.4% was mild and 14.2% moderate. There was no major depression. According to the distribution of depression by semesters, it was mainly present in the first 14.2%, second 10.4%, seventh 20% and eighth 15.2%. Conclusions: It was evidenced that most of the students surveyed course with some depressive symptom, mostly of moderate intensity, which may be influenced by various factors such as poor support networks, changes in lifestyle and stress generated by the academic semester load.